2012
DOI: 10.3109/03014460.2012.660990
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference is an accurate and simple index for evaluating overweight and obesity in Han children

Abstract: The present study demonstrates that NC is a simple, inexpensive and accurate measurement that may be used to identify overweight and obesity in Han children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 26 publications
10
43
2
6
Order By: Relevance
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study have shown that body weight and BMI have a positive correlation with NC, corroborating other studies conducted with children older than 2 years of age, in Brazil and other countries. 7,9,12,13,[15][16][17][18]20 The results of the present study also show that there was a moderate positive correlation between NC and BMI in both genders according to age group, supporting the results from studies conducted with Turkish, American and Chinese children. 7,12,18 However, some important limitations should be considered.…”
Section: Neck Circumference To Identify Excess Body Weight In Childresupporting
confidence: 88%
“…16 An additional advantage of using NC as a proxy for upper body fat distribution is that it shows no variation in size throughout the day. 7,12 Although several studies have been published that have examined NC as a measure for identifying excess body weight, 7,9,12,13,[15][16][17][18][19][20][21] to our knowledge, no study has been conducted with children under two years of age. The purpose of the present study was thus to evaluate the accuracy of NC as a measure for assessing excess body weight in children aged [13][14][15][16][17][18][19][20][21][22][23][24] and to provide NC data to help establish guidelines that can be used to identify excess body weight in children under two years of age.…”
Section: Introductionmentioning
confidence: 99%
“…14,18,19,27 These factors may preclude or at least decrease the feasibility of using other parameters (WC and HC). 14,18,19,27 On the other hand, these issues seem to be avoided during NC measurement.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,19,27 These factors may preclude or at least decrease the feasibility of using other parameters (WC and HC). 14,18,19,27 On the other hand, these issues seem to be avoided during NC measurement. 14,18,19,27 Moreover, it is possible to suggest that NC may be a more suitable means for anthropometric measurements among elderly people than other tools, since its evaluation can be performed with the subject in a seated position, with no need to use light clothing (thereby avoiding awkward moments Interestingly, even though the HTN condition was associated with large NC among elderly women, the hemodynamic measurements made at rest in the present study, except for MAP among elderly women, did not show any association with NC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation